The Development of Motor and Pre-literacy Skills by a Physical Education Program in Preschool Children: A Non-randomized Pilot Trial - Battaglia, Giuseppe; Alesi, Marianna; Tabacchi, Garden; Palma, Antonio; Bellafiore, Marianna (Frontiers in Psychology, 2019)
Unlike other European countries, Italian kindergartens do not include the physical education teacher in the school organic personnel. This is frequently associated with the lack of opportunities to perform physical education by preschool children. Moreover, in literature, it is very hard to find a specific physical education program (PEP) that could improve the preschool child’s motor and cognitive status. The aim of this study was to analyse the effects of a PEP on quotient of gross motor development (QGMD) and pre-literacy skills in preschool children. We conducted a school-based non-randomised pilot trial. It involved 119 preschool children, clustered in a control group (CG, n= 29, body mass index (BMI): 16.90±3.16) and an intervention group (IG, n= 90, BMI: 16.00±1.75). Participants were assessed for literacy readiness, locomotor and object control skills before and after the experimental period. IG increased the locomotor, object-control skills and QGMD by 24.40%, 9.70% and 10.40%, in response to PEP. The mean difference of the QGMD between CG and IG, in the pre and post period, was significantly higher for the IG (11.30 vs 3.20, p=0.0082). As concern pre-literacy skills, the analyses of gain scores and ANCOVA did not show any significant effect of the intervention. In conclusion the used PEP improves fundamental motor skills in preschool children. Consistently with the growing research, interventions based on scheduled physical exercises ensure health benefits for preschool children